Acoustic Diagnostics Applications in the Study of Technical Condition of Combustion Engine - Adam DEPTUŁA; Dariusz KUNDERMAN; Piotr OSIŃSKI; Urszula RADZIWANOWSKA; Radosław WŁOSTOWSKI (Archives of Acoustics, 2016)
The paper presents the possible applications of using acoustic diagnostics in inspecting the technical condition of an internal combustion engine with autoignition on the example of the Fiat drive unit with common rail system. As a result of measuring the sound pressure level for specific faults and comparing the noise generated by the motor running smoothly, the detailed maps of changes in the acoustic spectrum are possible to generate. These results may be helpful in the future diagnostics of internal combustion engines. In the paper, the results of scientific work in the area of research, design and operation of internal combustion engines, conducted at the Department of Automotive Engineering, in cooperation with the Laboratory of Hydraulic Drives & Vibroacoustics of Machines at the Wroclaw University of Technology are included.